(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
Background and Objectives: – The aim of this study was to evaluate the role of CT scan in evaluation of patients with traumatic head injury, to study the imaging spectrum of traumatic head injury, to study the relative prevalence of different traumatic head injury lesions.Methods: The study was prospective and was carried out between December 2019 and January 2020 at the Department of Radiology, AMC MET Medical College and Sheth L.G. Hospital, Ahmedabad. Total 50 patients having clinical history of traumatic head injury and sent to department of radiodiagnosis and diagnosed having abnormal findings on CT scan were included in the study. Confirmation of diagnosis by CT Scan done prior to data collection. (Only those patients were included who had traumatic head injury confirmed with history correlation and then were confirmed by CT scan.)Results: Out of 50 patients diagnosed by CT scan, the most common traumatic head injury seen in our study were- subarachnoid hemorrhage, subdural hematoma, epidural hematoma, skull fractures, pneumocephalus, scalp injures and focal areas of contusions/laceration. CT scan had an average specificity of 94%, with 100% specificity for common traumatic head injury like subdural hematoma.Conclusion: CT scan is a safe and effective method of detecting traumatic head injury. It aids in defining therapeutic decision quickly and allows predicting outcomes of the patient. High degree of specificity of CT scan diagnosis in the present study confirms the value of CT scan evaluation of traumatic head injury and suggests that it can be effectively used in the routine diagnostic work.